An overview of laser principle, laser–tissue interaction mechanisms and laser safety precautions for medical laser users - M. Jawad, Mohammed; Sarah T. , Abdul Qader; Zaidan, A. A.; Zaidan , B. B.; Naji, Ahmed Wathik; Ibraheem T. , Abdul Qader (A N S I Network, 2011)
Laser can now be regarded as practical and economical tool with unique properties that has been utilized effectively in several applications. Medical, dental, biological and various chemical and physical investigations use lasers due to their advantages. The medical laser systems offer the physician and the dentist not only a window, but also a door into this high technology which facilitate a lot of clinical and therapeutic applications. The user of the medical laser should understand the fact that there is no certain laser can be used for all tasks, therefore, it is important for the medical laser users to have a fundamental understanding of qualitative laser technology and essential operation of those lasers with biological tissues. In spite of their advantages, lasers have definite hazard by causing serious damage on the tissue of both patient and laser operation personnel. Due to this fact, laser users should study the laser hazards and safety precautions.